Analysis of LCL-Filter Performance in Three-level Full SiC NPC Inverters with Inductor Core Materials - Kang, Ho Hyun; Jo, Ha Rang; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2022)
This paper analyzes the performance of an LCL-filter according to inductor core materials in a three-level full silicon carbide (SiC) neutral point clamped (NPC) inverter. The three-level full SiC NPC inverter is operated with a high switching frequency due to low switching losses of SiC devices. To improve the output quality and system miniaturization, the LCL-filter is applied with the high switching frequency system. The inductor on the inverter side is more affected by the high switching frequency of the SiC NPC inverter compared to the grid side inductor. As a result, the core losses and temperature rising occur at the inverter side inductor and these lead to the efficiency reduction of the inverter. In this paper, the various core materials such as a super core, an amorphous core, and a powder core are analyzed considering to operating condition, system efficiency, size, and manufacturing ability. The LCL-filter performance depending on core materials is verified by the experimental results.
Keywords: Core material; Filter performance; High switching frequencies; LCL filters; Neutral-point clamped inverters; Paper analysis; Silicon carbide; Three-level; Three-level neutral point clamped; Three-level neutral point clamped inverte; Core materials; LCL-filter; Silicon carbide (SiC); Three-level NPC inverter